Characteristics of significant events identified by pharmacy students while on early immersion pharmacy practice experiences - Rodgers PT; Cheng V; Bush AB; Williams C (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Objective: The purpose of this study was to characterize and classify significant events of pharmacy students who completed an early practice experience. Methods: Significant event analyses (SEAs) were reflections submitted by students about events that they found impactful during their early practice experiences. An online repository has stored 287 SEAs submitted by first year pharmacy students for later use in a pharmacy course. For this study, all significant events were read and coded according to the pre-specified themes and tones (positive, negative, neutral, hybrids) of the event. Themes used were derived from prior literature characterizing major themes from other health professional students' experiences. Additional themes were added by authors for those that did not fit into the pre-set categories. All themes of the narratives were subsequently categorized. To assure confirmability, the investigators conferred to discuss new themes that emerged and events that were ambiguous. To assure credibility, an external audit of a sample of the coded SEAs was completed. Upon reaching consensus between primary reviewer and secondary reviewers, data were reported as frequencies and percentages. This study received ethics clearance from the Office of the University Registrar and was deemed exempt by the University Institutional Review Board. Results: A total of 1,055 coded responses were analyzed. The majority of SEAs were positive in tone (n=190, 66.2%) and many were hybrids of negative-turned-positive emotions (n=62, 21.6%). The most common major content theme was "patients and the provision of patient care" (n=412, 39.1%), followed by "pharmacy students and their behavior" (n=260, 24.6%). The most prevalent subthemes were "learning by doing" (n=134, 12.7%) and "feelings of usefulness or uselessness" (n=111, 10.5%). Conclusions: The majority of students framed significant events in their pharmacy practice experiences in a positive light, even from challenging interactions. The events that resonated most frequently with these students centered around patient interactions and providing patient care. These results will be useful for pharmacy educators developing pharmacy school curriculums to better prepare students to excel and feel more comfortable in direct patient care experiences.